Methodological Approach in Assessing the Level of Innovative Development of an Enterprise (On the Example of Housing and Communal Services Sphere) - E. A. Kuklina; O. S. Mitselovskaya (Управленческое консультирование)
In the context of the digital economy formation the level of innovative development of the enterprise is a marker of the readiness of the economic system for digital transformation. Digital transformation makes it possible to digitize all the aspects of the business that generate interfaces for interacting with clients and then digital technologies are used to obtain results through the implementation of innovative strategies and the production of innovative products. The results of the study in which the subject is the methodological aspects of assessing the level of innovative development of an enterprise are relevant. The article formulates the necessary conditions for ensuring the economic efficiency of enterprises of various industries and fields of activity (the availability of innovative potential, a sufficient level of innovative development, high readiness to develop and implement a leader’s strategy). The scientific hypothesis is the assumption that it is necessary to use a methodological approach based on the phased implementation of assessment procedures and the use of assessment methods corresponding to each stage. An algorithm for assessing the level of innovative development of an enterprise is proposed, the concept of innovative potential is clarified and its structure which takes into account the digital transformation of the economy is determined. The indicators of assessing innovative potential and the level of innovative development of the enterprise are substantiated. The proposed methodological approach was tested using the enterprises in the field of housing and communal services of the BFA Group management company.